Research progress on the chemical components and biological activities of sea cucumber polypeptides - Shou, Yiwen; Feng, Chao; Lu, Qinpei; Mao, Xin; Huang, Huisha; Su, Zhiheng; Guo, Hongwei; Huang, Zhaoquan (Frontiers in Pharmacology, 2023)
Owing to their unique physical and chemical properties and remarkable biological activities, marine biological resources are emerging as important sources of raw materials for producing health products, food, and cosmetics. Collagen accounts for approximately 70% of the sea cucumber body wall, and its hydrolysis produces small-molecule collagen polypeptides with diverse biological functions, such as anticancer, antihypertensive, immune-enhancing, memory-enhancing, and cartilage tissue repairing effects. Notably, the potential of sea cucumber polypeptides in combination with anticancer therapy has garnered considerable attention. Determining the composition and structure of sea cucumber polypeptides and exploring their structure–activity relationships will aid in obtaining an in-depth understanding of their diverse biological activities and provide scientific insights for the development and utilisation of these polypeptides. Therefore, this review focuses on the amino acid structures and activities of sea cucumber polypeptides of varying molecular weights. This study also provides an overview of the biological activities of various sea cucumber polypeptides and aims to establish a scientific basis for their development.